Phenotypic and Genetic Characterization for Incompatible Cross-Match Cases in the Feline AB Blood Group System - Uno, Yumiko; Yaguchi, Masami; Kobayashi, Tasuku; Onozawa, Eri; Ochiai, Kazuhiko; Yoshida, Karin; Nakamura, Chihiro; Udagawa, Chihiro; Omi, Toshinori (Frontiers in Veterinary Science, 2021)
The feline AB blood group system (blood types A, B, and AB) encoding the cytidine monophosphate-N-acetylneuraminic acid hydroxylase (CMAH) gene is the most significant in transfusion medicine and hemolysis of the newborn for cats. Blood typing and cross-matching in pre-transfusion testing are crucial to determining blood compatibility and thus prevent hemolytic transfusion reactions. We here performed serological and genetic investigations to characterize blood samples from cats with discordant results for card agglutination (CARD) and the alloantibody agglutination test for blood typing in two cats (subjects K and R). Subject K showed incompatible cross-matching in pre-transfusion testing. Red blood cells from subjects K and R determined blood type B from the CARD method showed blood type AB by alloanti-A and alloanti-B antibodies in agglutination testing. Genomic DNA sequencing of the coding region (exons 1a to 14) for the cat CMAH gene showed that subject K had four mutations with heterozygosity at c.139C>T, c.179G>T, c.327A>C, and c.364C>T. Similarly, the CMAH gene of subject R carried six mutations with heterozygosity at c.142G>A, c.187A>G, c.268T>A, c.327A>C, c.773G>A and c.1603G>A, representing a new diplotype including a novel synonymous single nucleotide polymorphism (SNP) in exon 7 (c.773 G>A: Arg258Gln). The CMAH diplotype in subjects K and R was different from major diplotype in blood type B cats. This study is the first to report CMAH variants in cats with discordant blood types between CARD and TUBE methods. These results could assist in the classification of feline AB blood types for transfusion medicine to avoid blood incompatibilities.